Dogs: From Predator to Protector - Andy Hirsch (First Second, 2017)
How well do you know our favorite furry companion? Did they really descend from wolves? What's the difference between a Chihuahua and a Saint Bernard? And just how smart are they? Join one friendly mutt on a journey to discover the secret origin of dogs, how genetics and evolution shape species, and where in the world his favorite ball bounced off to.
Keywords: Narrative Non-Fiction -- Narrative Non-Fiction